Pengaruh Budaya Kerja terhadap Efektivitas Kinerja Aparatur Kelurahan Kramat Selatan Kota Magelang - Asna Choirul Ibad; Kayla Trianda Putri N; Wenni Ayunadia; Desti Aryaningsih; Salsa Triya Ningrum (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This study aims to analyze the influence of work culture on the effectiveness of the performance of the Kramat Selatan Village apparatus in Magelang City. The study uses a quantitative approach, a causal associative research type. The study population consisted of 17 village apparatuses with a saturated sampling technique so that the entire population became respondents. Data collection was carried out through a questionnaire using a Likert scale and analyzed using SPSS. The results show that the work culture in the Kramat Selatan Village in Magelang City is in the good category. The majority of respondents gave a positive assessment of aspects of work independence, clarity of rules and procedures, leadership support, open communication, and encouragement of innovation within the organization. The effectiveness of the apparatus' performance is also in the good category as demonstrated by the ability to complete work effectively, increase work performance, adaptability, and responsive attitude to work changes. A conducive work culture also creates a more disciplined and cooperative work atmosphere and supports the creation of optimal public services for the community. These conditions indicate that the implementation of a good work culture can help apparatuses in improving service quality, strengthening work responsibilities, and creating more harmonious working relationships within the government organization environment. Research results show that a positive work culture can support increased effectiveness in the performance of civil servants in public service delivery. Therefore, strengthening work culture is carried out continuously through increasing coordination, discipline, and developing innovation in civil servant work.